(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Women constitute 48.4% of total population in India. A large proportion of women workforce is engaged in informal activities such as domestic helpers, labourers, local artisans etc. Their contribution in the economic growth is unrecognized. They are marginalized and deprived from resources. They have limited access to institutional credit, which pose hurdles in their financial inclusion. Financial inclusion is defined as the access to financial services at a reasonable cost.